BS EN 13501-3. Fire classification of construction products and building elements. Part 3. Classification using data from fire resistance tests on products and elements used in building service installations: fire resistant ventilation ducts and fire dampers and or power, control and communication cables (27th May 2021) - British Standards Institution,
No abstract available